Psychological prosperity among kindergarten students (Journal of the College of Basic Education, 2023)
The current research aims to identify the psychological prosperity of kindergarten students, and the research relied on the descriptive approach and the research sample consisted of (400) female students from the kindergarten department at Al-Mustansiriya University / College of Basic Education. The theories and previous studies related to the subject of their research, as it included the Psychological Prosperity Scale in its final form on (70) items, and the two researchers verified the psychometric characteristics of the tool. The two researchers reached the following results:The kindergarten students are characterized by psychological prosperity.There are no statistically significant differences in the psychological prosperity of the female students of the kindergarten department due to the variable of the academic stage.